Multimodal PSSMA-Functionalized GdF3 : Eu3+ (Tb3+ ) Nanoparticles for Luminescence Imaging, MRI, and X-Ray Computed Tomography - Shapoval, Oleksandr; Kaman, Ondřej; Hromádková, Jiřina; Vavřík, Daniel; Jirák, Daniel; Machová, Daniela; Parnica, Jozef; Horák, Daniel (ChemPlusChem, 2019)
Biocompatible poly(4-styrenesulfonic acid-co-maleic acid)-stabilized GdF3 : Eu3+ (Tb3+ ) nanoparticles were obtained by a one-step coprecipitation method in ethylene glycol or water. The particles are very small (3 nm), have a narrow size distribution, and were detectable by fluorescence, magnetic resonance, and X-ray contrast imaging. These properties allow multimodal imaging, which has prospective applications in the simultaneous and detailed detection of diseased tissues.
Keywords: Europium; Magnetic Resonance Imaging; Fluorides; fluoridy; optické zobrazování; Tomography, X-Ray Computed; terbium; magnetic resonance imaging; x-ray computed tomography; Nanoparticles; gadolinium fluoride; Maleates; magnetická rezonanční tomografie; europium; Optical Imaging; nanočástice; luminescence; maleáty; Terbium; polystyreny; gadolinium; Polystyrenes; biocompatible; Gadolinium; počítačová rentgenová tomografie